2022
DOI: 10.1111/luts.12428
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism is prevalent among adult women with chronic lower urinary tract symptoms

Abstract: Objective: To define the prevalence of hypothyroidism in women with chronic lower urinary tract symptoms (LUTS) and to compare the severity of each symptom between patients with hypothyroidism and controls. Subjects and methods:In this prospective observational study, we screened all adult women who came to the urology clinic between March 2017 and September 2020, and enrolled patients with chronic LUTS in the study. We assessed thyroid function.We evaluated the severity of voiding and storage urinary symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Our study shows a positive phenotypic and genetic association between thyroid diseases, female genital prolapse, and disorders of the bladder/urinary system. Individuals with thyroid problems often present lower urinary tract symptoms (Zargham et al, 2022). Although the topic has not been studied thoroughly and the exact mechanisms remain unclear, it is known that thyroid hormones also affect the gastrointestinal tract and kidney function (Frau et al, 2017; Iglesias et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows a positive phenotypic and genetic association between thyroid diseases, female genital prolapse, and disorders of the bladder/urinary system. Individuals with thyroid problems often present lower urinary tract symptoms (Zargham et al, 2022). Although the topic has not been studied thoroughly and the exact mechanisms remain unclear, it is known that thyroid hormones also affect the gastrointestinal tract and kidney function (Frau et al, 2017; Iglesias et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[64] Moreover, researchers found that there are also other endocrinopathies or endocrines associated with LUTS. For instance, by assessing the thyroid function of the female patients from March 2017 to September 2020, Zargham et al [65] found that the severity of stress urinary incontinence and storage symptoms might be related to hypothyroidism. In addition, Nicolson et al [66] discovered the possible relationship between estrogens and LUTS in males.…”
Section: Endocrinopathiesmentioning
confidence: 99%
“…For instance, by assessing the thyroid function of the female patients from March 2017 to September 2020, Zargham et al. [ 65 ] found that the severity of stress urinary incontinence and storage symptoms might be related to hypothyroidism. In addition, Nicolson et al.…”
Section: Luts Overviewmentioning
confidence: 99%